(untitled) (International Journal of Engineering and Computer Science, 2016)
This paper gives a new design of Acoustic Doppler Current Profiler (ADCP). It basically works on the principle of Doppler Effect. Development of Acoustic Doppler Current Profiler is given. Types of ADCP’s are depending on mounting are horizontally mounted ADCP’s and vertically mounted ADCP’s. Frequency shift measurement is the basic thing in ADCP. There are various algorithms available for frequency measurement of ADCP. Some are given in this paper. So this paper gives a detailed study of Acoustic Doppler Current Profiler. Only some components are required for the design. Further range of penetration is dependent on the type of ultrasonic sensor used. As we go on changing the sensor performance parametric will also change.